Penguins - Barrett, Norman S. (New York : F. Watts, 1991)
Depicts the habitats, feeding habits, life cycle, and different species of penguins.
Includes index.
School Library Journal.
5.6
3-5.
3-6
Keywords: Penguins -- Juvenile literature; Penguins; Penguins